(untitled) (Economics and region, 2024)
This article explores gender equality trends in the European Union, focusing on women’s participation in leadership roles, government cabinets, and political institutions, particularly the European Parliament. It shows that while gender equality at high levels of governance and business is improving, further efforts are needed for true equality. The study highlights an increase in women’s representation in government and political bodies, but they remain underrepresented in senior leadership roles, signaling the need for more proactive measures. In the European Parliament, a rising proportion of women reflects the effectiveness of gender-focused policies, though male dominance persists, requiring continued quotas and support programs. The analysis of women in leadership positions in major European companies shows progress, though full gender balance has yet to be achieved. More active corporate policies are needed to reduce gender imbalances. Overall, the article emphasizes the importance of continued efforts to ensure gender equality, focusing on career advancement and equal access to opportunities.